ULTRACAM: An ultrafast, triple-beam CCD camera for high-speed astrophysics - Dhillon, V; Marsh, T; Stevenson, M; Atkinson, D; Kerry, P; Peacocke, P; Vick, A; Beard, S; Ives, D; Lunney, D; McLay, SA; Tierney, C; et al. (2007)
ULTRACAM is a portable, high-speed imaging photometer designed to study faint astronomical objects at high temporal resolutions. ULTRACAM employs two dichroic beamsplitters and three frame-transfer CCD cameras to provide three-colour optical imaging at frame rates of up to 500 Hz. The instrument has been mounted on both the 4.2-m William Herschel Telescope on La Palma and the 8.2-m Very Large Telescope in Chile, and has been used to study white dwarfs, brown dwarfs, pulsars, black hole/neutron star X-ray binaries, gamma-ray bursts, cataclysmic variables, eclipsing binary stars, extrasolar planets, flare stars, ultracompact binaries, active galactic nuclei, asteroseismology and occultations by Solar System objects (Titan, Pluto and Kuiper Belt objects). In this paper we describe the scientific motivation behind ULTRACAM, present an outline of its design and report on its measured performance. © 2007 The Authors. Journal compilation © 2007 RAS.